Expressive Speech Act in Comic Bintang Emon’s Speech in Social Media about Social Distancing - Julisah Izar; M. Muslim Nasution; Rengki Afria; Neldi Harianto; Mar'atun Sholiha (Titian: Jurnal Ilmu Humaniora, 2021)
Abstract This research aims to describe speech act form of angry expressive spoken by Comic Bintang Emon in social media about social distanting. The method of this research is qualitative by describing the data. The data source of this research is Comic Bintang Emon’s speech in social media about social distancing. Collecting data in this analysis used technique of listening, data reduction, and data analysis. The data were analysed to see how the form of speech act was spoken by Bintang Emon and relatedness of speaker’s sociopragmatics. The result of this research is speech act of angry expressive spoken by Comic Bintang Emon used speech strateries: literal direct speech act and unliteral direct speech act. Literal direct speech act in the speech consisted of two speeches while non-literal direct speech act consisted of five speeches. Keywords: speech act, qualitative, angry expressive speech, strategy/ speech form